2017
DOI: 10.2495/safe-v7-n4-463-474
|View full text |Cite
|
Sign up to set email alerts
|

TRM reinforcement of masonry specimens for seismic areas

Abstract: This document analyses the resistant behaviour to diagonal compression and direct compression of brick masonry specimens, reinforced with textile reinforced mortars (TRM) and without them. The numerical models have been calibrated with experimental results in order to have a suitable technique to reinforce masonry historic constructions where extraordinary tension stresses could occur in seismic situations. For the numerical modelling, FEM models have been developed using non-linear layered bi-dimensional shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Different authors [18,19] have indicated that the use of TRM can overcome most of FRPs limitations. It has been evidenced that TRM is also more compatible with the substrate [20,21,22]. Recent research has been carried out on the application of TRM solutions to different masonry typologies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors [18,19] have indicated that the use of TRM can overcome most of FRPs limitations. It has been evidenced that TRM is also more compatible with the substrate [20,21,22]. Recent research has been carried out on the application of TRM solutions to different masonry typologies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the Chinese government has begun to pay attention to geological survey, and field scholars have increased understandings of the geophysical exploration methods. Per the requirements of various engineering and construction works in the country, the Ministry of Geology and Mineral Resources took the lead in carrying out research on high density resistivity method and its applications [12][13][14][15]. In both theory and practice, field scholars have discussed this method and solved a few difficulties related to it, also, some devices that fit the requirements at that time have been developed according to these research achievements [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, their application is now promising also in case of internal reinforcement, [1]. Alternatively, Fabric Reinforced Cementitious Matrix (FRCM) can be used, [2]- [6]. The state-ofknowledge about the FRP-confinement of masonry is summarized in [7]- [18] referring to different types of masonry (clay and natural stone) and FRPs (carbon and glass) and confining scheme (continuous and discontinuous).…”
Section: Introductionmentioning
confidence: 99%